Relevance of liver‐limited disease in metastatic colorectal cancer: Subgroup findings of the FIRE‐3/AIO KRK0306 trial. Issue 5 (7th November 2017) - Holch, Julian Walter; Ricard, Ingrid; Stintzing, Sebastian; Fischer von Weikersthal, Ludwig; Decker, Thomas; Kiani, Alexander; Vehling‐Kaiser, Ursula; Al‐Batran, Salah‐Eddin; Heintges, Tobias; Lerchenmüller, Christian; Kahl, Christoph; Kullmann, Frank; et al.
Abstract : In metastatic colorectal cancer (mCRC), liver‐limited disease (LLD) is associated with a higher chance of metastectomy leading to long‐term survival. However, limited data describes the prognostic and predictive relevance of initially unresectable LLD with regard to targeted first‐line therapy. The present analysis investigated the relevance of initially unresectable LLD in mCRC patients treated with targeted therapy against either the epidermal growth factor receptor (EGFR) or vascular epithelial growth factor (VEGF). The analysis was performed based on FIRE‐3, a randomized phase III trial comparing first‐line chemotherapy with FOLFIRI plus either cetuximab (anti‐EGFR) or bevacizumab (anti‐VEGF) in RAS wild‐type (WT) mCRC. Of 400 patients, 133 (33.3%) had LLD and 267 (66.8%) had non‐LLD. Median overall survival (OS) was significantly longer in LLD compared to non‐LLD patients (36.0 vs . 25.4 months; hazard ratio [HR] = 0.66; 95% confidence interval [CI]: 0.51–0.87; p = 0.002). In a multivariate analysis also including secondary hepatic resection as time‐dependent variable, LLD status was independently prognostic for OS (HR = 0.67; 95% CI: 0.50–0.91; p = 0.01). As assessed by interaction tests, treatment benefit from FOLFIRI plus cetuximab compared to FOLFIRI plus bevacizumab was independent of LLD status with regard to objective response rate (ORR), early tumour shrinkage ≥20% (ETS), depth of response (DpR) and OS (all p > 0.05). In conclusion, LLD could be identified as a prognostic factor in RAS‐WT mCRC, which was independent of hepatic resection in patients treated with targeted therapy. LLD had no predictive relevance since benefit from FOLFIRI plus cetuximab over bevacizumab was independent of LLD status. Abstract : What's new? Metastatic colorectal cancer (mCRC) patients with liver‐limited disease (LLD) have been described as optimal candidates for metastectomy leading to long‐term survival. However, few studies have evaluated the prognostic and predictive relevance of initially unresectable LLD treated with targeted first‐line therapy. Here, LLD was examined in RAS wild‐type mCRC patients enrolled in FIRE‐3, a trial comparing first‐line FOLFIRI plus either cetuximab (anti‐EGFR) or bevacizumab (anti‐VEGF). LLD constituted a prognostic factor, which was independent of secondary metastectomy. Furthermore, treatment response and survival were more favourable when using FOLFIRI plus cetuximab compared to bevacizumab, irrespective of LLD status.